Using Adipose Measures from Health Care Provider-Based Imaging Data for Discovery - Elliot D. K. Cha; Yogasudha Veturi; Chirag Agarwal; Aalpen Patel; Mohammad R. Arbabshirani; Sarah A. Pendergrass (Journal of Obesity)
The location and type of adipose tissue is an important factor in metabolic syndrome. A database of picture archiving and communication system (PACS) derived abdominal computerized tomography (CT) images from a large health care provider, Geisinger, was used for large-scale research of the relationship of volume of subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) with obesity-related diseases and clinical laboratory measures. Using a “greedy snake” algorithm and 2,545 CT images from the Geisinger PACS, we measured levels of VAT, SAT, total adipose tissue (TAT), and adipose ratio volumes. Sex-combined and sex-stratified association testing was done between adipose measures and 1,233 disease diagnoses and 37 clinical laboratory measures. A genome-wide association study (GWAS) for adipose measures was also performed. SAT was strongly associated with obesity and morbid obesity. VAT levels were strongly associated with type 2 diabetes-related diagnoses (p = 1.5 × 10−58), obstructive sleep apnea (p = 7.7 × 10−37), high-density lipoprotein (HDL) levels (p = 1.42 × 10−36), triglyceride levels (p = 1.44 × 10−43), and white blood cell (WBC) counts (p = 7.37 × 10−9). Sex-stratified tests revealed stronger associations among women, indicating the increased influence of VAT on obesity-related disease outcomes particularly among women. The GWAS identified some suggestive associations. This study supports the utility of pursuing future clinical and genetic discoveries with existing imaging data-derived adipose tissue measures deployed at a larger scale.